(3aQb GdWH dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3HYVge bGd(B: (3Ef GdJLQjI hMOgG Jcai aj Pdc hHYVge QCi Cf GdbjGS jYfi GdJLQHI hjSehf ef EbJUQ Ydi GdJLQHI CUMGH GdJLQHI, hcPdc ef jSJYed GdbjGS ojSehf CUMGH GdbjGS s
(3BNQgG (B:s
(3haj GdCeQGV GdJj JYGdLhfgG HGdCOhjI, adYdce SJYQahf gPG cdg HYO Cf de jcf CbfYce eG bdfGg HYO aj cJGHfG gPG , hCeG GdBf aeG bdfGg aj gPG GdHGH bO jcJaj Hg GdeJYdehf , hdPdc Effj CbWY GdcdGe aj gPG GdehVhY Je cJGH aQb GdWH dLGdjfhS s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bhHdJ HCUdjf SfI (B692(3g`s
(3hHgGeTgG JUMjMGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B168 s
Keywords: (3GdWHs